Spontaneous hepatic subcapsular biloma: Report of three cases with review of the literature - Majid MUSHTAQUE; Mohammad FAROOQ MIR; Parvez NAZIR; Parwez Sajad KHAN; Vidhi DADU; Lateef A DAR; Rayees A DAR; Samina Ali KHANDAY (Turkish Journal of Gastroenterology, 2019)
-